Shedding Light on Healing: IPLT as a Brief Intervention for Psychological Recovery from Bullying. A Single-subject ABA Study Using DASS-21 Indicators. - Bariyyah, Khairul; Ifdil, Ifdil; Muqodas, Idat; Soejanto, Laily Tiarani; Andrianie, Santy; Hilmi, Ikhsan (Pertanika Journal of Social Sciences & Humanities, 2026)
Bullying among students has been identified as a source of major educational and psychological issues, which most of the time result in depression, anxiety, and stress. Despite increasing concern about bullying-related trauma, empirical evidence on brief and perceptual-based counselling interventions for psychological recovery remains limited. This research focused on determining the effectiveness of the Ifdil Perceptual Light Technique (IPLT), a trauma-informed counselling method used to alleviate the psychological impact of bullying. Through a single-subject A-B-A design, five students who scored highly on DASS-21 were monitored during baseline, intervention, and follow-up stages. The IPLT intervention consisted of five brief sessions lasting approximately 10-15 minutes each. Both visual and quantitative analyses showed substantial reductions in depression, anxiety, and stress, which were corroborated by effect size, Percentage of Non-Overlapping Data (PND), and Reliable Change Index (RCI) results. Social validation observed changes in emotional well-being, sleep quality, confidence, and social interaction. These findings suggest that IPLT may provide a promising approach for facilitating emotional recovery from bullying-related trauma. Due to its short and organised sessions, IPLT may offer a viable brief intervention for school counselling contexts. Additional research with a bigger sample size and longer follow-up periods is needed to ascertain the duration of the effects.